Optimal echo time for functional MRI of the infant brain identified in response to noxious stimulation - Goksan, S; Hartley, C; Hurley, S; Winkler, A; Duff, E; Jenkinson, M; Rogers, R; Clare, S; Slater, R (Wiley, 2016)
Purpose: Blood oxygen level dependent (BOLD) brain activity, measured using functional MRI (fMRI), is dependent on the echo time (TE) and the reversible spin–spin relaxation time constant (T! 2 ) that describes the decay of transverse magnetization. Use of the optimal TE during fMRI experiments allows maximal sensitivity to BOLD to be achieved. Reports that T! 2 values are longer in infants (due to higher water concentrations and lower lipid content) have led to the use of longer TEs during infant fMRI experiments; however, the optimal TE has not been established. Methods: In this study, acute experimental mildly noxious stimuli were applied to the heel in 12 term infants (mean gestational age ¼ 40 weeks, mean postnatal age ¼ 3 days); and the percentage change in BOLD activity was calculated across a range of TEs, from 30 to 70 ms, at 3 Tesla. In addition, T! 2 maps of the whole brain were collected in seven infants. Results: The maximal change in BOLD occurred at a TE of 52 ms, and the average T! 2 across the whole brain was 99 ms. Conclusion: A TE of approximately 50 ms is recommended for use in 3T fMRI investigations in term infants. M